Effects of ω-3 PUFAs Supplementation on Myocardial Function and Oxidative Stress Markers in Typical Rett Syndrome. (12th January 2014) - Maffei, Silvia; De Felice, Claudio; Cannarile, Pierpaolo; Leoncini, Silvia; Signorini, Cinzia; Pecorelli, Alessandra; Montomoli, Barbara; Lunghetti, Stefano; Ciccoli, Lucia; Durand, Thierry; Favilli, Roberto; Hayek, Joussef
Abstract : Rett syndrome (RTT) is a devastating neurodevelopmental disorder with a 300-fold increased risk rate for sudden cardiac death. A subclinical myocardial biventricular dysfunction has been recently reported in RTT by our group and found to be associated with an enhanced oxidative stress (OS) status. Here, we tested the effects of the naturally occurring antioxidants ω -3 polyunsaturated fatty acids ( ω -3 PUFAs) on echocardiographic parameters and systemic OS markers in a population of RTT patients with the typical clinical form. A total of 66 RTT girls were evaluated, half of whom being treated for 12 months with a dietary supplementation of ω -3 PUFAs at high dosage (docosahexaenoic acid 71.9 ± 13.9 mg/kg b.w./day plus eicosapentaenoic acid 115.5 ± 22.4 mg/kg b.w./day) versus the remaining half untreated population. Echocardiographic systolic longitudinal parameters of both ventricles, but not biventricular diastolic measures, improved following ω -3 PUFAs supplementation, with a parallel decrease in the OS markers levels. No significant changes in the examined echocardiographic parameters nor in the OS markers were detectable in the untreated RTT population. Our data indicate that ω -3 PUFAs are able to improve the biventricular myocardial systolic function in RTT and that this functional gain is partially mediated through a regulation of the redox balance.